2022
DOI: 10.1111/jdv.18513
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset vitiligo after COVID‐19 mRNA vaccination: A causal association?

Abstract: Dear Editor, Given the widespread vaccination of the population with the novel mRNA vaccines against COVID-19, it is of utmost importance to identify any possible adverse effects they may have. In clinical trials with the BNT162b2 COVID-19 mRNA vaccine (Pfizer-ΒioNTech), adverse effects included mostly injection-site reactions, fatigue and headache. 1 Herein, we report a case of vitiligo following vaccination with the BNT162b2 COVID-19 mRNA vaccine (Pfizer/ BioNTech).A 69-year-old male presented with white mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Regarding other cutaneous diseases developed following COVID-19 vaccination available or reported in literature, we have found nine cases of morphea [ 218 , 219 , 220 , 221 , 222 , 223 ], and 11 cases of vitiligo [ 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 ]. Other dermatoses have been described, such as chilblains, pityriasis lichenoides et varioliformis acuta, Henoch–Schönlein purpur, lichen striatus or Rowell syndrome, Sweet Syndrome, dermatomyositis, and exanthematous pustulosis.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding other cutaneous diseases developed following COVID-19 vaccination available or reported in literature, we have found nine cases of morphea [ 218 , 219 , 220 , 221 , 222 , 223 ], and 11 cases of vitiligo [ 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 ]. Other dermatoses have been described, such as chilblains, pityriasis lichenoides et varioliformis acuta, Henoch–Schönlein purpur, lichen striatus or Rowell syndrome, Sweet Syndrome, dermatomyositis, and exanthematous pustulosis.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review included and analyzed 14 studies. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] We observed hetero- COVID-19 vaccines, regardless of their design, rely on presenting the SARS-CoV-2 spike glycoprotein (SP) antigen to induce immunological memory and neutralizing antibodies. 21 Studies have revealed similarities between fragments of the SARS-CoV-2 SP and mammalian proteins, especially human (Homo sapiens) proteomes.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, we analyzed a total of 26 patients with vaccine‐associated vitiligo following COVID‐19 vaccination. The systematic review included and analyzed 14 studies 3–16 . We observed heterogeneity in both patient characteristics and the vaccines implicated in postvaccine vitiligo occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, seven case reports have been reported regarding the newly developed vitiligo following COVID-19 vaccination. 1,[4][5][6][7][8][9] Vitiligo is a disease characterized by the immune-mediated loss of epidermal melanocytes. 10 The relationship between the COVID-19 vaccination and the onset of vitiligo and the instances of autoimmune responses after vaccination suggest that the COVID-19 vaccines may play a role in vitiligo progression, 5 but with limited evidence.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 vaccine has also been considered a potential trigger of autoimmune reactions such as immune thrombocytopenic purpura (ITP), a phenomenon in which platelets are targeted for destruction by the autoimmune system 3 . In addition, seven case reports have been reported regarding the newly developed vitiligo following COVID‐19 vaccination 1,4–9 . Vitiligo is a disease characterized by the immune‐mediated loss of epidermal melanocytes 10 .…”
Section: Introductionmentioning
confidence: 99%